Pengaruh Metode SPEOS (Stimulasi Pijat Endorfin Oksitosin Suggestif) Terhadap Produksi ASI Pada Ibu Nifas - Elisa Elisa; Latifah Lely Septiariani; Kurniati Puji Lestari (Indonesian Journal of Nursing Research (IJNR), 2020)
Health profile of Semarang in 2018, the exclusive feeding of the exclusive breast milk in the age of 0-6 months of 65.57%. It’s still far from Central Java target of 80%. This problem of breastfeeding influenced by reduced stimulation of oxytocin hormones, while physical and psychological changes can affect the lactation process. One of the efforts to increase the breast milk production with SPEOS (Suggestive Endorphin Oxytocin Massage Stimulation). The SPEOS method can help nifas mother to facilitate the expenditure of breast milk. To know the effect of the SPEOS method (Suggestive Endorfin Oxytocin Massage Stimulation) on Breast Milk Production in Nifas Mothers. The research design used quasy experiment with one group pre-post test. Sample in this study was nifas mother with spontaneous childbirth amounted to 27 people. The sampling technique used consecutive sampling. Breastfeeding production before mothers performed SPEOS method on average was 3.70 ml with standard deviation of 5,113. Breast milk production after mother performed SPEOS method on average was 129,63 ml with standard deviation 11,001. There was an influence of SPEOS method to breast milk production on nifas mother at Maternity Hospital of Mardi Rahayu Semarang (p-value = 0,000). Stimulation Massage Endorphin Oxytocin SuggestifBreastmilk Production,Nifas Mother